INDONESIAN TRADE IMPORTS AND CHANGES IN CONSUMER BEHAVIOR FROM AMERICAN TO KOREAN FOOD STYLE TOWARDS FOOD CONSUMPTION - Prawidya Hariani RS; Reynaldi Putra Adila (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The problem in this study is the phenomenon of changes in consumption behavior in food, which initially the people of Medan City preferred American Style food, changing to preferring Korean Style food, this causes a change in consumption behavior in society. The main objective of this study is to analyze what factors cause behavioral changes and analyze the indicators that have been determined in food consumption to Korean food style. This type of research uses qualitative data through primary data by snowball sampling from non-probability samples using a Likert scale, to produce descriptive data. The use of Smart-PLS software is used to process the data. Indonesia's trade with the United States and South Korea has increased over time, including food from both countries. The results achieved are the decision to consume Korean food, all 4 indicators meet, but the indicator remains American food reaching 0.587, the rest achieve validity> 0.829. Furthermore, for Convergent validity, the 4 factors, namely Culture, Personal, Social and Psychological, all meet> 0.865. The results of the hypothesis test show that all factors also meet at> 0.05. So the conclusion is that young people in Medan City are experiencing a change in their food consumption behavior from American to Korean Food Style but have not completely abandoned their older food.